Capacity building for sustainable development - James, Valentine Udoh, 1952- (CABI, 2018)
This book provides a comprehensive analysis of how to build capacity in tackling many sustainable development problems in Africa. The book's approach is both theoretical and applied. It offers methods of operationalizing sustainable development and sustainability theories and explores capacity building methods at different levels of government. The book has 23 chapters and covers different fields such as sustainable agriculture, sustainable tourism, rural development, environmental impact analysis, women empowerment, sustainable energy, education for sustainable development, and climate change adaptation, among others